(untitled) (Research, Society and Development, 2022)
Food irradiation has been shown to be efficient in terms of controlling pathogens in minimally processed foods and increasing the shelf life of these products. The present work aimed to evaluate the action of different radiation doses and storage temperatures on minimally processed, pre-cooked and vacuum-packed carrots. The samples were submitted to gamma radiation in a 60Co Multipurpose source at the Institute of Energy and Nuclear Research at doses of 0 kGy (control); 1.0 kGy; 2.0 kGy and 3.0 kGy and stored at room temperature, refrigerator (5°C±1°C) and freezer (-18°C±1°C). The physicochemical parameters analyzed were: soluble solids content, titratable acidity, pH, color, total carotenoids and firmness. These analyzes were performed once a week for a period of three weeks. The statistical method used was analysis of variance (significance level of 5%), followed by Tukey’s test. It was found that the use of the irradiation process, for most cases, did not significantly affect the physicochemical parameters of the analyzed samples. Titratable acidity and pH were the parameters most influenced by the use of different radiation doses throughout the storage period. An increase in pH values was observed in treatments with radiation doses. Lower storage temperatures (refrigerator and freezer) were more efficient in maintaining the characteristics of the products throughout the storage period. In general, the doses of 1kGy and 3kGy were the ones that presented values closer to those of the control for the analyzed parameters.